1991
DOI: 10.1063/1.349165
|View full text |Cite
|
Sign up to set email alerts
|

Surface analysis of reactive ion-etched InP

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…16 and Bae et al 17 used ex-situ XPS to characterize the surface of InP samples etched with HBr/Ar and Cl 2 /Ar inductively coupled plasmas, respectively, and reported the presence of InBr x and InCl x products in the In 3d core level spectrum, as well as a significant reduction of peak intensity in the P 2p core level spectrum. On the other hand, some ex-situ XPS surface analysis conducted for Cl 2 -based capacitively coupled reactive ion etching (CCP-RIE) 18 and various electron cyclotron resonance (ECR) or ICP etching chemistries including Cl 2 , 19,20 Cl 2 /CH 4 /H 2 , 20 or HBr/O 2 9 gas mixtures have shown that a P-rich surface can also be obtained, but the origin of P enrichment was not identified. Phosphorus enrichment was also reported after chemical cleaning/etching of InP.…”
Section: Introductionmentioning
confidence: 98%
“…16 and Bae et al 17 used ex-situ XPS to characterize the surface of InP samples etched with HBr/Ar and Cl 2 /Ar inductively coupled plasmas, respectively, and reported the presence of InBr x and InCl x products in the In 3d core level spectrum, as well as a significant reduction of peak intensity in the P 2p core level spectrum. On the other hand, some ex-situ XPS surface analysis conducted for Cl 2 -based capacitively coupled reactive ion etching (CCP-RIE) 18 and various electron cyclotron resonance (ECR) or ICP etching chemistries including Cl 2 , 19,20 Cl 2 /CH 4 /H 2 , 20 or HBr/O 2 9 gas mixtures have shown that a P-rich surface can also be obtained, but the origin of P enrichment was not identified. Phosphorus enrichment was also reported after chemical cleaning/etching of InP.…”
Section: Introductionmentioning
confidence: 98%
“…A sidewall polymer creating gas such as CH 4 or SiCl 4 ͑the latter in conjunction with a photoresist mask͒ is added to prevent undercutting, and other gases such as H 2 may be added to optimize the surface morphology and stoichiometry. 13,[22][23][24][25][26][27][28][29][30][31] Similar work needs to be performed for the GaAs/AlGaAs system. While Cl 2 -containing plasma chemistries are generally employed for GaAs, there has been little investigation into optimizing the etching under high microwave power conditions in the type of electron cyclotron resonance ͑ECR͒ single-wafer reactors now finding increasing application in III-V device technology.…”
Section: Introductionmentioning
confidence: 99%
“…1 On InP, it was shown that RIE can produce a change of surface stoichiometry ͑depletion of P͒. [2][3][4] Also, passivation of dopant elements by hydrogen was reported. 4,5 However, extended systematic studies of deep-level defects created by RIE are still scarce.…”
Section: Introductionmentioning
confidence: 99%